FUND CHARACTERISTICS AND FUND MANAGER SKILLS AS DETERMINANTS OF MUTUAL FUND PERFORMANCE: EVIDENCE FROM SHARIA EQUITY FUNDS IN INDONESIA (International Conference on Social and Islamic Studies, 2022)
As a country with the largest Muslim majority population in the world, Indonesia is the most potential target market for sharia-based products. This is indicated by the increasing public enthusiasm for various sharia investment products. There are two aims of this study. First aim is to evaluate the performance of sharia equity funds in Indonesia by employing risk-adjusted returns as the measurement and its investment manager’s competence. Second aim is to provide empirical evidence whether fund characteristics such as fund size, expense ratio, and portfolio turnover ratio, together with fund manager skills such as stock selection skill and market timing ability have influence on fund performance. This study used a sample of 15 sharia equity funds in Indonesia with an observation period from 2017-2021. Secondary data of fund characteristics is available on annual financial report contained in the sustainability prospectus of each sample. Meanwhile, secondary data of portfolio return, market return, and risk-free rate for measuring fund manager skills and fund performance can be obtained from pasardana.id and Bank Indonesia official website. Data analysis technique used in this study is descriptive analysis and panel data multiple regression analysis. This study provides additional empirical evidence in the field of sharia capital market investment that is beneficial for future researchers, and also useful for sharia-compliant investors as another important reference regarding factors that can significantly influence sharia equity fund performance.